Paleomagnetic study of the Mount Riiser-Larsen area in Enderby Land, East Antarctica - Ishikawa, Naoto; Funaki, Minoru (National Institute of Polar Research, 2000)
P(論文) Paleomagnetic analyses were performed on samples of two sites from felsic gneiss of the Archaean Napier Complex and two sites from a dolerite dike (Amundsen dikes) in the Mt Rnser-Larsen area in Enderby Land, East Antarctica As a result of progressive demagnetization experiments, directions of the high-stability (H) components, carried probably by fine-grained magnetite, were determined for one dolerite and two gneiss sites Among the three sites, gneiss samples at the two sites were found to be magnetically amsotropic, while magnetic fabrics at the dolerite site indicated the possibility that the fabrics are of primary origin Based on the results of demagnetization experiments and magnetic amsotropy measurements, the H component direction of one dolerite site was regarded as a primary one Virtual geomagnetic poles of two sites form the dolerite dikes in this study and Ishikawa and Funaki (1998) appeared to be situated near the segment of the apparent polar wander path between 1 0 and 1 2 Ga for Australia in the East Gondwanaland frame It might be implied that East Antarctica and Australia formed East Gondwanaland at the time of igneous activity of the Amundsen dikes departmental bulletin paper